Radiological Anatomy of the Pelvis and Pelvic Limb of the Greater Cane Rat (Thryonomys swinderianus) - Faraja H. Mpagike; Modesta Makungu (Veterinary Medicine International)
Greater cane rats (Thryonomys swinderianus) are now being captive reared and domesticated in the sub-Saharan Africa because of increase in their demand for biomedical research and traditional medicine and as a source of meat. This research was performed to provide the normal radiological anatomy of the pelvis and pelvic limb in greater cane rats for a reference in biomedical research, in anatomical studies, and in clinical use. Radiological examination of the pelvis and right pelvic limb was done in five greater cane rats. Radiological results were correlated with bones of the pelvis and right pelvic limb. The pelvic bone had a prominent caudoventral iliac spine. The pelvic symphysis was long and obturator foramina appeared teardrop-shaped elongated craniocaudally. The prominent major trochanter extended proximally higher than the femoral head. The middle third of the body of the tibia presented a very prominent tuberosity. In all specimens, the tarsal sesamoid bone was visualised. Mineralised popliteal sesamoid bone was not visualised. In male greater cane rats, the os penis was visualised. The lateral and medial menisci of the stifle joint were seen with ossicles. The first metatarsal bone was rudimentary with greater plantar divergence. Despite of the pelvic limb and pelvis of greater cane rats sharing anatomical structures with other rodents, it retains some exceptional anatomical features. Findings of this study will serve as a reference for anatomical studies, clinical veterinary practice, and in biomedical research.